ANALISIS VOLUME IMPOR GULA INDONESIA DENGAN REGRESI DATA PANEL PERIODE 2010 ‐ 2015 - Thomy Rizky Setiawan; Made Siti Sundari; Idfi Setyaningrum (Perpustakaan Universitas Surabaya, 2018)
Sugar is one of the product from agriculture sector of the estatesubsector and is designated as a special commodity in the World TradeOrganization (WTO) negotiation forum. Demand for sugar in Indonesia is higherthan production so sugar imports are still needed to fulfill the demand. Ithappened because factors that support sugar production in Indonesia still notoptimal. This research aims to determine and analyze what factors can affect theimport of sugar in Indonesia in the period 2010-2015. This research used paneldata which is combination of time series data and cross-section period 2010-2015obtained from the Central Bureau of Statistics (BPS) and data from other partieswho are ready to be processed. The analysis model used is Data Panel Regression.Using panel data in regression has several advantages, namely: bigger degree offreedom, able to accommodate heterogeneity levels, dynamic data, effect size,build and trial complicated model and minimize bias. Research result show GDP,Import Value, and Exchange Rate can affect Indonesian Sugar Import Volume,while for Sugar Production partially have a positive influence on Indonesian SugarImport Volume but the value is not significant.